Faktor-Faktor Penentu Struktur Modal serta Dampaknya Terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia dan Bursa Efek Malaysia ) - Mas'ud, Masdar (Jurnal Aplikasi Manajemen, 2009)
Results of research indicate that the factors of capital structure determiners have significant effect on capital structures such as profitability, size, growth opportunity, asset structure, and cost of financial distress. The exception may be tax shields effects without significant effect at all on capital structure. The latter becomes evident because the depreciation and amortization rates of Indonesia listed manufacturing companies do not seem significant to contribute company cash flow such that it stands out of company debt proportion. In Malaysia, the factors of capital structure determiners with significant effect on capital structures involve profitability, size, asset structure, cost of financial distress and tax shields effects. Size and growth opportunity do not have significant effect on the capital structure because Malaysia manufacturing companies consider little investment rate to finance equity financing to deal with financial risk regardless the size of company. It shows the similarity of these factors of capital structure determiner between manufacturing companies listing at Indonesia Stock Exchange and Malaysia Stock Exchange. The significantly similar determiner factors pertain to growth opportunity, asset structure and company value. Meanwhile, the difference also develops between the factors of capital structure determiner in the manufacturing companies listing at Indonesia Stock Exchange and Malaysia Stock Exchange. The significantly different determiner factors will be profitability, size, cost of financial distress, tax shields effects and capital structure.